VCP-DCV for vSphere 7.x. (Pearson IT Certification, 2021)
9+ Hours of Video Instruction Almost 10 hours of video designed to help you prepare to pass the VMware Professional vSphere 7.x exam, which is a key requirement for earning the VCP-DCV certification. This course is also advantageous to those who want to learn how to implement, configure, and manage a vSphere environment or those preparing to take another Data Center Virtualization qualifying exam. Overview Earning the VCP-DCV certification demonstrates that you can implement, configure, manage, and support virtual infrastructure and clouds built on VMware vSphere 7. It demonstrates that you understand the components, features, and use cases for vSphere 7. The major step for earning VCP-DCV is to pass the Professional vSphere 7 exam. This course is designed to help you achieve exam success! It provides details on the exam objectives as stated in the exam blueprint, as well as technical detail, explanations, and real-world examples. At the end of each lesson is an end-of-lesson quiz to test your understanding of the concepts discussed. Throughout this course, you will gain a deeper understanding of VMware vSphere 7 and how to use it to implement virtual compute infrastructure, virtual storage infrastructure, and virtual network infrastructure. You learn how to optimize host clusters and provide high availability for VMs to protect against hardware, storage, and network infrastructure issues. You learn how to monitor virtual machines and vSphere components and how to perform day-to-day operations and maintenance. At the end of the course, you will not only be able to engage in knowledgeable discussions involving vSphere 7 but also will be well on your way to passing the Professional vSphere 7.x exam and be that much closer to VCP-DCV certification. About the Instructor John A. Davis, an independent contractor and senior integration architect at MEJEER, LLC, became a VMware Certified Instructor (VCI) and VMware Certified Professional (VCP) in 2004. Since then, all of his work has focused on VMware-based technologies. He has experience in teaching official VMware curriculum in five countries and delivering VMware professional services throughout the United States. Recently, his work has involved designing and implementing solutions for hybrid clouds, cloud automation, disaster recovery, and virtual desktop infrastructure (VDI). He has authored several white papers and co-authored the VCP6-DCV Cert Guide and the VCAP5-DCA Cert Guide (VMware Press). He holds several advanced certifications, including VCAP5-DCA, VCAP5-DCD, VCAP5-DTD, VCAP5-CID, and VCIX6-NV. He has been a vExpert since 2014. He is author of the vLoreBlog.com and can be found on Twitter @johnnyadavis. Skill Level Intermediate/Advanced Learn How To Best prepare for the VCP-DCV 7.x exam Implement, configure, and manage a vSphere environment Install ESXi and vCenter Server Configure SSO Leverage storage infrastructure with vSphere Manage virtual storage infrastructure for your VMs Provide virtual network infrastructure for your VMs Keep everything secure in vSphere Use the various vSphere resources and tools Deploy, modify, and use VMs Use Virtual Machine File Structure and VM Snapshots Upgrade VMware Tools and VM virtual hardware Migrate virtual machines, both hot and cold Clone VMs Upgrade vSphere and implement Lifecycle Management best practices Who Should Take This Course Anyone hoping to pass the VCP-DCV 7.x exam A person with 6-12 months of hands-on experience implementing, managing, and supporting a vSphere environment, including knowledge of storage, networking, hardware, security, business continuity, and disaster recovery concepts Current and prospective IT professionals such as system administrators, infrastructure administrators, and virtualization engineers Course Requirements 6-12 months of hands-on experience implementing, managing, and supporting a vSphere environment, including knowledge of storage, networking, hardware, security, business continuity, and disaster recovery concepts Lesson Descriptions Lesson 1, "Exam Details and General Recommendations," focuses on the exam itself, including the purpose and requirements of the VCP-DCV certification, delivery options, the number of exam questions, and the objectives, resources, and recommendations. Lesson 2, "vSphere Overview, Installation, and Integration," starts with what the major pieces and editions of vSphere are, and the requirements for implementing vSphere. Then we cover vSphere in SDDC and hybrid clouds followed by vSphere integration with other VMware Products. Lesson 2 explains how to install ESXi as well as vCenter Server. Next, it covers Single Sign-on and how to configure it, and then covers the initial vSphere configuration. Lesson 3, "Storage Infrastructure, Configuration, and Management," deals with storage infrastructure. By the end of this lesson, you will have a good understanding of how to leverage storage infrastructure with vSphere and how to manage virtual storage infrastructure for your VMs. Lesson 4, "Network Infrastructure, Configuration, and Management," teaches you how to provide a virtual network infrastructure for your VMs. The lesson starts with network terminology and then delves into virtual switches, including vSphere standard switches and vSphere distributed switches. Next, the lesson covers VMkernel virtual adapters, TCP/IP stacks, networking policies, port allocation, binding, mirroring, network IO control, private VLANs, LACP support, and finally, managing hosts with vDS. Lesson 5, "vSphere Security," starts with vSphere certificates, including the key vSphere components that manage certificates and custom certificates. It then moves into vSphere Authentication and Single Sign-on (SSO). vSphere permissions, including default and custom roles, are next, and then security, which includes ESXi security, vCenter Server security, network security, and VM security. Lesson 6, "Cluster Configuration, Resource Management, and Optimization," covers vSphere DRS, which provides load balancing and VM happiness; vSphere DRS rules and resource pools, which controls VM placement and resource usage; and vSphere high availability and HA response. Other vSphere availability features are discussed, including vCenter Server HA, using performance charts, as well as other resource usage tools. This lesson also provides details on vSphere alerts and vSphere logging. Lesson 7, "Managing vSphere Services and Virtual Machines," provides many "how-to" steps for daily management and operational procedures involving vSphere inventory, virtual machine configuration and use, virtual machine file structure and VM snapshots, virtual machine upgrades, and virtual machine migrations. This lesson specifically focuses on two migration types: vMotion and Storage vMotion. Next, we cover virtual machine cloning and templates, the Content Library, vSphere upgrades and lifecycle management, and vCenter Server monitoring and management. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.